Understanding how food safety risk perception influences dietary decision making among women in Phnom Penh, Cambodia: A qualitative study - Brown, S.M.; Hung Nguyen-Viet; Grace, Delia; Ty, C.; Samkol, P.; Sokchea, H.; Pov, S.; Young, M.F. (BMJ, 2022)
Objectives To determine women’s perception of the risk of food safety and how it relates to diet, health and decision making as part of formative research for a market-based intervention that aims to improve the safety of animal-source foods sold in informal markets.